Discovery of Natural Product‐Based Fungicides (III): Semisynthesis and Biological Activity of N‐Phenylpyrazole Sarisan Hybrids as Antifungal Agents. Issue 1 (7th December 2021) - Hou, Enhua; Han, Meiyue; Wang, Xiaoguang; Cheng, Wanqing; Cao, Jiangping; Yang, Ruige; Guo, Yong
Abstract: Many phytopathogenic fungi can easily infect crops, resulting in crop yield reductions. In continuation of our efforts to develop natural product (NP)‐based antifungal agents, a series of N ‐phenylpyrazole sarisan hybrids 6a –v were prepared via I2 ‐mediated oxidative cyclization, and their structures were determined by various spectral analyses including IR, 1 H‐NMR and ESI‐MS. Among all N ‐phenylpyrazole sarisan hybrids, compounds 6a, 6b, 6e, 6i, 6j and 6r exhibited more encouraging antifungal action against at least two phytopathogenic fungi than the reference fungicide hymexazol. Especially, 6a displayed really encouraging and broad‐spectrum antifungal activity against F. graminearum, V. mali, and F. oxysporum f.sp.niveum with the EC50 values of 12.6±0.9, 18.5±0.2, and 37.4±1.8 μg/mL, respectively. Moreover, the structure‐activity relationships (SARs) were also observed. Additionally, compounds 6a and 6e also exhibited relative low toxicity on normal LO2 cells. This study indicates that these N ‐phenylpyrazole sarisan hybrids would shed light on developing novel NP‐based antifungal agents. Abstract :